Erythropoietin (EPO) increases myelin gene expression in CG4 oligodendrocyte cells through the classical EPO receptor. - Cervellini, I; Annenkov, A; Brenton, T; Chernajovsky, Y; Ghezzi, P; Mengozzi, M (2013)
Erythropoietin (EPO) has protective effects in neurodegenerative and neuroinflammatory diseases, including in animal models of multiple sclerosis, where EPO decreases disease severity. EPO also promotes neurogenesis and is protective in models of toxic demyelination. In this study, we asked whether EPO could promote neurorepair by also inducing remyelination. In addition, we investigated whether the effect of EPO could be mediated by the classical erythropoietic EPO receptor (EPOR), since it is still questioned if EPOR is functional in nonhematopoietic cells. Using CG4 cells, a line of rat oligodendrocyte precursor cells, we found that EPO increases the expression of myelin genes (myelin oligodendrocyte glycoprotein [MOG] and myelin basic protein [MBP]). EPO had no effect in wild-type CG4 cells, which do not express EPOR, whereas it increased MOG and MBP expression in cells engineered to overexpress EPOR (CG4-EPOR). This was reflected in a marked increase in MOG protein levels, as detected by Western blot. In these cells, EPO induced by 10-fold the early growth response gene 2 (Egr2), which is required for peripheral myelination. However, Egr2 silencing with a siRNA did not reverse the effect of EPO, indicating that EPO acts through other pathways. In conclusion, EPO induces the expression of myelin genes in oligodendrocytes and this effect requires the presence of EPOR. This study demonstrates that EPOR can mediate neuroreparative effects.